2020
DOI: 10.1002/jmrs.450
|View full text |Cite
|
Sign up to set email alerts
|

Identifying predictors of patient radiation dose during uterine artery embolisation

Abstract: Introduction: Uterine artery embolisation (UAE) is regarded as a safe and effective treatment for symptomatic uterine fibroids and/or adenomyosis. Dose reduction during UAE is critical for this reproductive-age patient population to minimise the risks of radiation-induced effects. The aim of this study was to identify the predictors of radiation dose which can be controlled and optimised for patients during UAE. Methods: A total of 150 patients between June 2018 and August 2019 were included in this study. Dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…A Pearson's correlation matrix was also undertaken to show any significant bivariate correlations between the independent variables included in the regression analysis. An MLR with stepwise elimination (25) was performed using the following predictor variables: BMI, number of fibroids, total fibroid volume, total uterus volume, Ka, r, fluoroscopy time, total DSA dose, total CRM dose, and total fluoroscopy dose. Scatter plots of the predictor variables and KAP were visually checked to confirm the assumption of a linear association between the predictor variables and KAP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A Pearson's correlation matrix was also undertaken to show any significant bivariate correlations between the independent variables included in the regression analysis. An MLR with stepwise elimination (25) was performed using the following predictor variables: BMI, number of fibroids, total fibroid volume, total uterus volume, Ka, r, fluoroscopy time, total DSA dose, total CRM dose, and total fluoroscopy dose. Scatter plots of the predictor variables and KAP were visually checked to confirm the assumption of a linear association between the predictor variables and KAP.…”
Section: Discussionmentioning
confidence: 99%
“…Under these specific conditions, it was found that total DSA (digital subtraction angiography), total CRM (conventional roadmap), and total LIH (last-image hold) dose as a function of the total procedural KAP were the significant radiation dose predictors identified following multivariable linear regression (MLR) analysis. (25) However, the upgraded system no longer records LIH dose or saved fluoroscopy information in contrast to its previous generation. There is a paucity of literature based on the formulation of regression models for UAE (25)(26)(27) or the application of the identified radiation dose predictors to optimise UAE practice (28) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has formed part of a QA process which has progressed to further studies which aim to fully implement this CQI program for optimising radiation dose during UAE by clinically validating the resultant regression model. 9 The results have demonstrated significant dose reduction, which is critically important for these reproductive‐age UAE patients. This demonstrates that implementing CQI programs to improve quality of care can be beneficial to many medical imaging department procedures.…”
mentioning
confidence: 96%
“…A previous study, 9 as part of an overall CQI program by the authors of this editorial, identified dose predictor variables for the interventional radiology procedure uterine artery embolisation (UAE). This has formed part of a QA process which has progressed to further studies which aim to fully implement this CQI program for optimising radiation dose during UAE by clinically validating the resultant regression model.…”
mentioning
confidence: 99%